IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN SEJARAH DI SMAN 1 KANDIS KABUPATEN SIAK - Khoiri, Jamiatul; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The 2013 curriculum is a curriculum that emphasizes on character education, especially at the basic level that will form the foundation at the next level. This curriculum has been implemented at SMAN 1 Kandis in Siak Regency since 2018. Implementation of the 2013 curriculum is an extension of the education level one (SBC) curriculum. This research aims to, (1) To find out the Implementation of History Learning in Curriculum 2013 at SMAN 1 Kandis Regency, (2). To find out the factors affecting the learning of History in the implementation of the 2013 curriculum in SMAN 1 Kandis Siak District, (3). To find out the supporting factors in learning History in implementing the 2013 curriculum in SMAN 1 Kandis Siak District, (4). To find out student feedback on History Learning in the 2013 curriculum at SMAN 1 Kandis Siak District. In this study we used qualitative descriptive method as a reference to conduct research on Curriculum Implementation 2013 In History Subjects At SMAN 1 Kandis. Qualitative research aims to gain a holistic view of something based on the viewpoint of the person being studied. Qualitative research relates to the ideas, perceptions, opinions or beliefs of the person being researched. The research period starts from the submission of the proposal title to the completion of the author's thesis. The result of this study is the implementation of the 2013 curriculum in learning history at SMAN 1 Kandis in Siak District. Key Words: Curriculum 2013 in SMAN 1 Siak district